Menciptakan Brand Evangelism: Studi Peran Brand Experience, Brand Relationship Quality dan Brand Loyalty - Siti Nurhasbiyah; Puji Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Brand Evangelism is an important role for companies or sellers because it can be a reason to give positive reviews and increase company sales. The purpose of this study is to analyze the effect of brand experience on brand loyalty, and assess its impact on brand relationship quality and brand evangelism. In addition, this study identifies the effect of brand image on brand loyalty and assesses the role of brand image as a mediator in the relationship between brand experience, brand relationship quality, and brand loyalty. The method used for sampling was purposive sampling involving 220 users of Apple products. Data analysis was carried out using the Principal Least Square - Structural Equation Modeling (PLS-SEM) method with SmartPLS 4. The results of this study prove that brand experience has a positive effect on brand evangelism and brand relationship quality. Then, brand experience has a positive effect on brand image. Meanwhile, brand relationship quality has a negative effect on brand evangelism. Furthermore, brand relationship quality has a positive effect on brand loyalty and brand image. And brand image has a positive effect on brand loyalty. Finally, brand loyalty has a positive effect on brand evangelism. This research is expected to provide insight into the importance of brand experience in improving the quality of brand relationships, forming a positive brand image, and strengthening customer loyalty. In addition, this research will also provide strategic recommendations for companies in creating effective brand evangelism.